Humidity Sensor of D-shaped Silver-coated Optical Fiber based on SPR Effect - GUO Xiangyu; ZHANG Zuxing (Guangtongxin yanjiu)
【Objective】In order to obtain a higher sensitivity fiber optic humidity sensor,this paper proposes a humidity sensor of D-shaped silver (Ag)-coated optical fiber based on Surface Plasmon Resonance (SPR) effect.【Methods】Graphene Oxide (GO) is coated on the surface of D-shaped Ag-coated optical fiber. Since GO has water absorption characteristics and the effective Refractive Index (RI) will change after absorbing water, SPR will be excited when certain conditions are met. Therefore, it can be used as a humidity sensor. In order to obtain the maximum SPR sensitivity of the sensor, the structure of D-type Ag-coated optical fiber is firstly modeled by COMSOL Multiphysics software, and the influence of polishing depth and Ag film thickness on the sensing characteristics is explored by finite element analysis. Then the structure is verified by experiments Validity and rationality of parameters. Finally, a layer of GO film is coated on the surface of the D-shaped Ag-coated optical fiber to explore its performance of humidity detection.【Results】The simulation results show that the optimal sensor structure is the polishing depth of 58.4 μm, the thickness of the Ag film is 50 nm, and the maximum wavelength sensitivity of 5 500 nm/RIU is obtained between the ambient RI of 1.34 and 1.40. On the basis of this parameter, the RI sensing characteristics are verified through experiments. The sensor has a maximum wavelength sensitivity of 3 668 nm/RIU, and the R square value is 0.98, which has good linearity. After coating the GO film on the surface, the humidity sensitivity of 0.545 nm/%RH is obtained when the relative humidity changes from 30% to 90%, and the linear R-squared values under the two conditions of increasing and decreasing relative humidity are 0.961 1 and 0.971 1, respectively.【Conclusion】The simulation results and the actual experiment have the same resonance peak change range, which shows the effectiveness and rationality of the sensor.GO isolates the Ag film from contact with air, preventing oxidation. The optical fiber humidity sensor obtained by combining its water-absorbing properties with the SPR properties of the metal film demonstrates high sensitivity, providing a novel approach for the development of highly sensitive humidity sensors.